Crowdsourcing and probabilistic decision-making in software engineering - Gupta, Varun, 1987- (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2020)
"This book examines crowd-based software engineering. It explores effective solutions, automation supports, and case studies about crowd-based software engineering"--